Evaluation of the effects of added vitamin D3 in maternal diets on sow and pig performance - Flohr, Joshua R.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Nelssen, Jim L.; Bergstrom, J. R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 84 sows (PIC 1050) and their litters were used to determine the effects of supplementing high levels of dietary maternal vitamin D3 on sow and pig performance, serum 25(OH)D3, milk vitamin D3, neonatal bone mineralization, and neonatal tissue vitamin D3. After breeding, sows were randomly assigned to 1 of 3 dietary vitamin D3 treatments (680, 1,360, or 2,720 IU/lb of complete diets). Sows were bled on d 0 and 100 of gestation, and at farrowing and weaning (d 21). Pig BW was recorded at birth and weaning, and serum was collected from 2 pigs/litter at birth, on d 10, and at weaning. A total of 54 piglets (18/treatment) were euthanized at birth and necropsied to sample bones and tissues. Sow and suckling pig performance and neonatal bone ash and bone density did not differ (P > 0.10) among maternal vitamin D3 treatments, but sow serum 25(OH)D3 and milk vitamin D3 increased (linear, P < 0.01) with increasing maternal vitamin D3 supplementation. Piglet serum 25(OH)D3 increased (quadratic, P < 0.03) with increased maternal vitamin D3. Neonatal kidney vitamin D3 tended (quadratic, P = 0.08) to decrease with increasing maternal vitamin D3, but liver vitamin D3 tended (linear, P = 0.09) to increase with increasing maternal vitamin D3; however, physiological concentrations of vitamin D within these tissues were low regardless of statistical tendencies. At weaning, a subsample of 180 pigs (PIC 327 × 1050) were used in a 3 × 2 split plot design for 35 d to determine the effects of maternal vitamin D3 and 2 levels of dietary vitamin D3 (816 or 8,160 IU/lb) from d 0 to 10 postweaning on piglet growth and serum 25(OH)D3. Overall (d 0 to 35), nursery ADG and F/G were not affected by either source of vitamin D3, but ADFI tended (quadratic, P < 0.06) to decrease with increasing maternal vitamin D3 because pigs from sows fed 1,360 IU of vitamin D3/ lb had lower ADFI compared with pigs from sows fed 680 or 2,720 IU vitamin D3/ lb. Nursery pig serum 25(OH)D3 increased (linear, P < 0.01) with increasing maternal vitamin D3 on d 0 (weaning), and maternal × diet interactions (P < 0.01) were observed on d 10 and 21 because pigs from sows fed 680 IU vitamin D3/lb had greater increases in serum 25(OH)D3 when fed 8,160 IU vitamin D3/lb compared with pigs from sows fed 1,360 IU vitamin D3/lb. In conclusion, sow and pig serum 25(OH)D3 and milk vitamin D3 can be increased by increasing maternal vitamin D3, and nursery pig serum 25(OH)D3 can be increased by increasing dietary vitamin D3; however, sow and pig performance and neonatal bone mineralization was not influenced by increasing vitamin D3 dietary levels.
Keywords: Serum 25(OH)D3; Vitamin D3; Sow performance; Pig performance